Empowerment Community: Gerakan Literasi Digital dalam Mendukung Taman Harati sebagai Edutourism di Desa Bukit Liti, Kecamatan Kahayan Tengah, Kabupaten Pulang Pisau - Ali Sunarno; Dotrimensi; Yuana Ledy Prilia; Muhammad Darwin; Andes Cintia Nungrum; Triyani (Jurnal Pengabdian Kampus, 2025)
Villages hold a strategic position in national development, particularly in Indonesia. The tourism sector is an effective way to develop villages and improve community welfare. Village tourism development often utilizes a community empowerment approach. Edutourism, or tourism integrated with education, is a promising approach to developing the tourism sector in Indonesia. Digital transformation has become a crucial instrument in accelerating village development, particularly in the education-based tourism sector. Therefore, the development of a digital literacy movement is a crucial factor in developing Harati Park as an edutourism destination in Bukit Liti Village. To achieve this, several programs were implemented, including Socialization and Field Orientation, Photography and Promotional Content Training, Videography and Promotional Content Training, and Promotional Content Editing Training. Evaluation results revealed that participants gained increased knowledge, skills, and insight in creating photography, videography, and content editing. This serves as a foundation for developing Harati Park as an edutourism destination in Bukit Liti Village.